STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI ANAK TUNAGRAHITA - Fauzul Andim; A.Saiful Aziz (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2021)
AbstractEducation is the right of all citizens regardless of origin, caste or physical condition of a person, including children with disabilities. As mandated in the Constitution Number 20 of 2003 concerning the National Education System in article 5 paragraphs 1 and 2 it is stated that "Every citizen has the same right to obtain quality education and "Every citizen who has physical, mental, intellectual and or social workers have the right to special education” (UU Sisdiknas 2003). Therefore, Islamic religious education must also be given to children with special needs, one of which is mentally retarded children, of course in the learning process using different learning strategies from the learning strategies applied to formal school students.Keywords: Mental retardation, Learning StrategyAbstrakPendidikan sebagai hak seluruh warga negara tanpa membedakan asal-usul, kasta maupun keadaan fisik seseorang, termasuk anak-anak yang memiliki kecacatan. Sebagaimana di amanatkan dalam UUD Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional pada pasal 5 ayat 1 dan 2 dinyatakan bahwa “Setiap warga negara mempunyai hak yang sama untuk memperoleh pendidikan yang bermutu dan “Setiap warga Negara yang memiliki kelainan fisik, mental, intelektual dan atau sosial berhak memperoleh pendidikan khusus” (UU Sisdiknas 2003). Oleh sebab itulah pendidikan agama Islam juga harus diberikan kepada anak berkebutuhan khusus salah satunya adalah anak Tunagrahita, tentunya dalam proses pembelajarannya menggunakan strategi pembelajaran yang berbeda dengan strategi pembelajaran yang diterapkan pada siswa sekolah formal.Kata kunci: Tunagrahita, Strategi Pembelajaran